God has Always Been the Luo's God - Ogot, Madara (Anyange Press Ltd, Kisumu, Kenya, 2026)
Is it possible that the God worshipped by the Southern Luo as Nyasaye is the very same God revealed in the Old Testament as Yahweh? This groundbreaking book answers that question with depth, humility, and startling clarity. Drawing on Scripture, Luo oral tradition, anthropology, and a covenant understanding of God, the book presents profound parallels between Nyasaye and Yahweh, both described as Creator, Judge, Protector, and Giver of rain, fertility, and life. From the Southern Luo taboos of kwer and chira to the covenant blessings and curses of Leviticus, from ancestral mediators to Israel’s prophets, the evidence reveals a shared divine moral order. More than a cultural comparison, this book is a compelling spiritual journey that affirms God’s presence among all nations and invites readers to rediscover their heritage with reverence and confidence. Whether you are Luo, Christian, a student of world religions, or simply curious about how God reveals Himself across cultures, this book will challenge, inspire, and deepen your understanding of the One true God known in Luo tradition as Nyasaye and in Scripture as Yahweh.
Keywords: Religion; Luo; Nyasayism; Nyasaye